IMPROVEMENT OF PEDAGOGICAL MECHANISMS OF DEVELOPMENT OF HEALTHY LIVING CULTURE OF WOMEN IN FAMILY AND NEIGHBORHOODS - Jumasheva Aruxan Xamidulla qizi (Galaxy International Interdisciplinary Research Journal, 2023)
One of the wonderful traits of the Uzbek people is respecting and honoring women. In order to improve the position and status of women in society, Uzbekistan is currently engaged in historical projects of great national significance. After all, the attitude toward and attention paid to women, youth, and families is tied to the stability and development of the political and socio-spiritual environment in society. In this article, there are thoughts and opinions about the improvement of pedagogical mechanisms for the development of a healthy culture of women and girls in families and neighborhoods.